2018
DOI: 10.1166/jnn.2018.14880
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Feature of Pluronic F127 and Its Application in Burn Treatment

Abstract: The morphological features of pluronic F127 at various concentrations were investigated and 20% aqueous pluronic F127 solution was chosen for the preparation of biomembrane. The pluronic solution was mixed with appropriate concentration of excipients such as PVA, Povidon S630, PG, Nipagin, Neomycin and Panthenol. The prepared pluronic F127 was thermosensitive, a liquid phase at low temperatures (≤10 °C) but converting into gel at temperatures above 20 °C, and formed stable biomembrane at 37 °C. The neomycin im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Using a rat model, we found that BSP effectively prevented the development of restenosis in venous bridges. Pluronic-F127 gel is a commonly used drug-carrying gel that is inherently stable and has no inhibitory effect on restenosis in blood vessels 24,25 . Therefore, in this study, we used pluronic-F127 as a carrier for BSP in order to investigate the effect of BSP on restenosis in venous bridge vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rat model, we found that BSP effectively prevented the development of restenosis in venous bridges. Pluronic-F127 gel is a commonly used drug-carrying gel that is inherently stable and has no inhibitory effect on restenosis in blood vessels 24,25 . Therefore, in this study, we used pluronic-F127 as a carrier for BSP in order to investigate the effect of BSP on restenosis in venous bridge vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Poloxamer F127 is broadly utilized as an adjuvant in the medical field. . In its application as a hydrogel matrix, the poloxamer F127 solution (approximately 20–40%) maintains a liquid state at low temperatures (approximately 4–5 °C) and a gelatinous state at body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl acrylate hyaluronic acid (HAMA) was also added to improve the mechanical properties of the 3D structures. There are some researchers chose 20% pluronic F127 aqueous solution to prepare biofilms [ 151 ]. After the neomycin-impregnated pluronic solution was mixed with polyvinyl alcohol (PVA) excipients (Povidon S630, PG) with appropriate concentration, the prepared neomycin-impregnated pluronic membrane inhibited the growth of bacteria on the agar plate through the sustained release of neomycin.…”
Section: Synthetic Polymers For Organ 3d Printingmentioning
confidence: 99%